A new species of Colacus Ohaus, 1910 (Coleoptera: Scarabaeidae: Dynastinae) from the Mata Seca biotope of Brazil, and notes on Colacus morio Ohaus, 1910 - Sobral, Rafael; de Morais, José W.; Grossi, Paschoal C. (Zootaxa, 2019)
In this contribution, Colacus rubrofemoratus Sobral, Morais, & Grossi new species (Coleoptera: Scarabaeidae: Dynastinae: Agaocephalini) is described and illustrated based on male specimens found in a transitional area of Caatinga, Atlantic Forest, and Cerrado in Brazil. In addition, the female of Colacus morio Ohaus, 1910 is redescribed, a distribution map for the genus is provided, and a new key to the species of Colacus is presented.